2018
DOI: 10.21315/mjms2018.25.1.8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Audio-Visual Cueing (Traffic Light) on Dual Task Walking in Healthy Older Adults and Older Adults with Balance Impairments

Abstract: Background: The walking gait of older adults with balance impairment is affected by dual tasking. Several studies have shown that external cues can stimulate improvement in older adults' performance. There is, however, no current evidence to support the usefulness of external cues, such as audio-visual cueing, in dual task walking in older adults. Thus, the aim of this study was to investigate the influence of an audio-visual cue (simulated traffic light) on dual task walking in healthy older adults and in old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Ageing may impair physical and cognitive functions, leading to the need for broader parking spaces and signals for street crossing. Audio-visual signals provide meaningful stimulation, which could be related to walking faster across the street [ 56 , 57 ]. It is suggested that auditory and visual signals be installed at signal-controlled junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Ageing may impair physical and cognitive functions, leading to the need for broader parking spaces and signals for street crossing. Audio-visual signals provide meaningful stimulation, which could be related to walking faster across the street [ 56 , 57 ]. It is suggested that auditory and visual signals be installed at signal-controlled junctions.…”
Section: Discussionmentioning
confidence: 99%
“…To amplify cognitive performance or mitigate the rate of age-related cognitive decline, social interaction, regular physical activity, and cognitive stimulation have been used [ 1 , 4 ]. There is no consensus, however, about type and duration of exercise programs to improve or mitigate cognitive decline [ 7 , 8 ] and yet less is known about the combined effects of exercise and cognitive stimuli in dual task to improve cognition and functional capacity in healthy [ 9 , 10 , 11 , 12 ] or unhealthy [ 13 , 14 , 15 ] older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Existem diversos artigos na literatura que avaliam uma marcha durante situações semelhantes a travessia de rua (Beurskens & Bock, 2012;Dommes & Cavallo, 2011;Dommes, Cavallo, Dubuisson, Tournier, & Vienne, 2014;Hatfield & Murphy, 2007;Kaewkaen et al, 2018;Nasar, Hecht, & Wener, 2008;Neider et al, 2011;Neider et al, 2010;Oxley, Ihsen, Fildes, Charlton, & Day, 2005), mas nenhum deles avaliam idosos mais velhos (acima de 80 anos de idade), sendo assim, é extremamente importante conhecer as adaptações da marcha necessárias para a realização dessa tarefa em cada faixa etária e desta forma entender o processo de envelhecimento nas multitarefas relacionadas a travessia de rua.…”
Section: Marcha E Travessia De Ruaunclassified